Organically Produced Foods - A Competitive Approach for the Twenty-First Century in Terms of Blue Ocean New Strategic Concept - George PLESOIANU; Alexandru - Costin CÎRSTEA (Revista de Management Comparat International)
The Blue Ocean Strategy provides a systematic approach to transform the competition in a less significant factor. This new concept provides companies and entrepreneurs ways to circumvent the fierce competition in the markets where there is a growing number of competitors with a relatively constant number of consumers by creating new market niches without competition. In fact, the strategy tries to extend the traditional and established market (called red oceans). Thus, tense and competitive market ( where economic activity is defined and accepted, and the competitive rules of the game are known) is avoided and Blue Ocean companies don’t fight to beat rivals for grabbing a segment of the potential demand. In these circumstances, the strategic orientation of small farmers and food processors to organic farming can be a leap to approach a new market area, almost non-existent in Romania, but with well defined demand especially in the intraCommunity market. Furthermore, the food industry multiplies its efforts to develop healthier and more sustainable products, in order to reduce the negative influence that junk food has on generating major diseases of the mankind (cancer, diabetes and obesity).